Integrated Diabetes Self-Management Program Using Smartphone Application: A Randomized Controlled Trial. (April 2022) - Kim, Yeojin; Lee, Hyejin; Seo, Ji Min
This study identified the effects of an integrated diabetes self-management program using smartphone application (app), based on the Information-Motivation-Behavioral skills (IMB) model. A randomized comparison, using a pre-and post-test design, was conducted with 32 participants in the experimental group and 36 in the control group. The integrated diabetes self-management program consisted of face-to-face educational sessions, a diabetes self-management smartphone app, and phone counseling. In the experimental group, diabetes self-management knowledge (Z=-2.70, p =.007), social motivation (Z=-1.97, p =.048), and behavior (t=3.22, p =.002) improved, with their hemoglobin A1c (Z=-4.83, p <.001) decreasing compared to the control group. At the post-test, the experimental group's fasting blood sugar level (t=2.79, p =.009), total calorie intake (t=3.94, p =.001), carbohydrate intake (t=5.69, p< .001), and fat intake (t=2.54, p =.021) decreased compared to the pre-test. An integrated diabetes self-management program using smartphone app, based on the IMB model, should be utilized as a nursing intervention.